The first 24-hour bilirubin level as a predictor of hyperbilirubinemia in healthy term newborns - Rina Triasih; Ekawaty L Haksari; Achmad Surjono (Paediatrica Indonesiana, 2003)
Background Early discharging healthy term newborns results ina difficulty to recognize hyperbilirubinemia.Objective The aim of this study was to determine the value of thefirst 24-hour total and unbound bilirubin levels in predicting hyper-bilirubinemia in healthy term newborns.Methods The first 24-hour and the 5 th day total and unboundbilirubin levels were measured in 84 healthy term newborns. Thetotal bilirubin level was measured spectrophotometrically, whereasunbound bilirubin level was determined by peroxidase-oxidationmethod. Hyperbilirubinemia was defined as serum total bilirubin of>12.9 mg/dL or serum unbound bilirubin of >0.5 mg/dL after 24hours of life.Results A correlation between the first 24-hour and the 5 th daytotal bilirubin levels was found (r= 0.53) with a regression equa-tion: Y (total bilirubin on day 5) = 4.69 + 1.15X (total bilirubin in thefirst 24 hours). In unbound bilirubin (r=0.31), the regression equa-tion was Y (unbound bilirubin on day 5) = 0.13 + 0.95X (unboundbilirubin in the first 24-hours). The relative risk for developing hy-perbilirubinemia in newborns whose TB 1 was >4.5 mg/dL was 12(95% CI 2.9;48.4), whereas newborns whose UB 1 was >0.09 mg/dL was 9.5 (95% CI 1.2;77.4).Conclusion Total bilirubin level of >4.5 mg/dL in the first 24 hourscan predict the development of hyperbilirubinemia in term new-borns in the first week of life. Newborns with such level of totalbilirubin need a longer stay or should visit the hospital on day 5-7